Friction stud riveting (FSR) of thick high-strength aluminum alloy structure. (June 2022) - Shan, He; Yang, Bingxin; Ma, Yunwu; Lou, Ming; Feng, Qiaobo; Li, Yongbing; Lin, Zhongqin
Abstract: 7-series aluminum (Al) alloy is a promising material that can meet the ever-increasing lightweight demand for transportation tools. However, the assembly between Al alloy and steel components brings challenges to the existing stud pre-embedded technology. This study proposes a friction stud riveting (FSR) process to achieve high-performance and high-efficiency embedding of steel studs in Al alloy parts by shank undercut, grooves interlock, and intermetallic compounds bonding. The stud geometry and FSR process were first optimized by evaluating the macro morphology of the joints. Then, the microscopic characterizations were performed to understand the material flow behavior, plastic deformation, and microstructure evolution of the joint induced by the feeding and rotation of the stud. The results indicate that the transient thermo-mechanical coupled FSR process leads to a continuous transition of sliding, mixed sliding-sticking, and sticking contact conditions between the stud and the Al alloy, resulting in a thermo-mechanical affected zone (TMAZ) outside the stud and a trapped Al alloy (TAA) inside the stud with diverse dynamic recrystallization (DRX) states and microstructures. The rotation state evolution and temperature gradients of the material within the TAA create two DRX bands that dominate the fracture behavior of TAA under tensile and shear loads. The strengths of the optimized steel stud-thick Al FSR joints reach 101.3% and 118.5% of the 7A52 Al alloy base material in tensile and shear tests, respectively, which solves the problem of low joining strength between steel stud and Al alloy plate due to the brittle and thick intermetallic compounds layers in conventional stud welding processes. Graphical abstract: Image 1 Highlights: Friction stud riveting process is proposed for steel stud-thick Al plate joining. Shank macro-undercut and grooves micro-interlock form the primary bearing capacity. The DRX grain refinement and interfacial solid-phase joining enhance the FSR joint. The strength of FSR joints is greater than that of 7A52 base metal.